A comparative study of Ilizarov ring fixators and limb reconstruction system fixators in the treatment of compound tibial shaft fractures - Lone, Aadil H.; Bhat, Aamir N.; Rather, Aabid A.; Maajid, Saheel; Khan, Kafeel (International Journal of Research in Orthopaedics, 2023)
Background: Tibia is the most commonly fractured long bone, and the prevalence of compound fractures has risen due to an increase in high-energy traumatic incidents. In addressing challenging tibial fractures with significant soft tissue damage, infected tibial nonunion, and compound tibial fractures, medical professionals have turned to specialized treatments, such as Ilizarov ring fixators and limb reconstruction system fixators. These fractures typically cannot be managed effectively with traditional internal fixation methods. To facilitate early weight-bearing, limb lengthening, and efficient wound care, two minimally invasive fixation systems have been developed: the Limb Reconstruction System and the ring fixator. Methods: The study was conducted on 40 patients with compound tibial shaft fractures treated by Ilizarov ring fixators and limb reconstruction system fixators with the aim to evaluate the functional outcome, union rate and amount of limb lengthening using Ring and ILRS fixators in compound tibial fixators. Results: In our study, a significant portion of the participants fell within the age range of 28 to 37 years, comprising 45% of the total sample. Furthermore, the majority of the study subjects were male, constituting 65% of the participant pool. The primary mode of injury reported in our study was road traffic accidents, accounting for 77.5%. Conclusions: The study concluded that LRS fixators show good and promising results like easy to apply, carry, compress, distract and clean while Ilizaro ring fixator is technically demanding, difficult to carry and cumbersome to the patient.